Determination of economically justified parameters of synchronous disconnection at low-voltage circuit switching via a synchronous vacuum contactor - A.V. Verkhola (National Technical University "Kharkiv Polytechnic Institute", 2014)
Dependence of a single switching procedure cost upon the contact opening delay time and delay-time spread is derived for a low-voltage synchronous vacuum contactor. For different cost levels, boundaries of permissible values of delay-time and delay-time spread are specified.